Does neuropsychological performance in OCD relate to different symptoms? A meta‐analysis comparing the symmetry and obsessing dimensions. Issue 8 (19th June 2018) - Bragdon, Laura B.; Gibb, Brandon E.; Coles, Meredith E.
Abstract : Background: Investigations of neuropsychological functioning in obsessive‐compulsive disorder (OCD) have produced mixed results for deficits in executive functioning (EF), attention, and memory. One potential explanation for varied findings may relate to the heterogeneity of symptom presentations, and different clinical or neurobiological characteristics may underlie these different symptoms. Methods: We investigated differences in neuropsychological functioning between two symptoms groups, obsessing/checking (O/C) and symmetry/ordering (S/O), based on data suggesting an association with different motivations: harm avoidance and incompleteness, respectively. Ten studies (with 628 patients) were included and each investigation assessed at least one of 14 neuropsychological domains. Results: The S/O domain demonstrated small, negative correlations with overall neuropsychological functioning, performance in EF, memory, visuospatial ability, cognitive flexibility, and verbal working memory. O/C symptoms demonstrated small, negative correlations with memory and verbal memory performance. A comparison of functioning between symptom groups identified large effect sizes showing that the S/O dimension was more strongly related to poorer neuropsychological performance overall, and in the domains of attention, visuospatial ability, and the subdomain of verbal working memory. Conclusions: Findings support existing evidence suggesting that different OCD symptoms, and their associated core motivations, relate to unique patterns of neuropsychological functioning, and, potentially dysfunction in different neural circuits.